Systematic Investigations of the Huperzine A—Producing Endophytic Fungi of Huperzia serrata in China and Fermentation Optimization Using OSMAC Strategy - Wei Li; Zhicheng Wang; Qiuyu Zhu; Pingfang Tian (Molecules, 2025)
Huperzine A (HupA) can alleviate Alzheimer’s disease due to its reversible inhibition of acetylcholinesterase (AChE). The chemical synthesis and plant extraction of HupA is plagued by route complexity and resource scarcity, respectively. Although some endophytic fungi from Huperzia serrata can independently biosynthesize HupA, their yields are trivial. After a comprehensive investigation of HupA-producing H. serrata across China, we focused on the endophytic fungi from Hunan and Hubei provinces, which demonstrated high-level HupA. Morphological characteristics and internal transcriptional sequence (ITS) analysis revealed their diversity. Among the four HupA-producing endophytic fungi, Colletotrichum kahawae is the best-performing and was thus subjected to fermentation optimization. When its fermentation medium was supplemented with H. serrata flavonoids daidzein and apigenin, HupA yields reached 58.38 μg/g (dry cell weight, dcw) and 72.21 μg/g dcw, respectively. In contrast, the addition of L-lysine and H. serrata extracts led to yields of 50.17 μg/g dcw and 255.32 μg/g dcw, respectively. Transcriptomic analysis revealed that H. serrata extracts substantially upregulated the expression of HupA biosynthesis genes in C. kahawae. Overall, H. serrata extracts outperformed L-lysine, daidzein, and apigenin in boosting HupA production, as they encompass all the necessary nutrients for C. kahawae growth. This study not only connotes a nutritional exchange between H. serrata and C. kahawae during long-term coevolution but also offers insights for harnessing plant extracts for the overproduction of desired metabolites in endophytic fungi.